Demotivating Semi-Compatibilism - Kevin Timpe (Ideas y Valores)
In this paper, I explore some of the motivations behind John Martin Fischer's semi-compatibilism. Particularly, I look at three reasons Fischer gives for preferring semi-compatibilism to libertarianism. I argue that the first two of these motivations are in tension with each other: the more one is moved by the first motivation, the less one can appeal to the second, and vice versa. I then argue that Fischer's third motivation ought not move anyone to prefer Fischer's semi-compatibilist picture to any of the leading contemporary libertarian theories. Finally, I make some methodological comments about the role intuitions play in Fischer's project.